1)
2)
3)
6)
С модулями, если честно, не помню как решать:(
Пошаговое объяснение:
4) (а+2b-4)+|-2|+а+2 = a+2b -4 +2 +a + 2 = 2a + 2b
5) (4b+1)-|-а-1|+b-1 = 4b+1-(a+1)+b-1 = 4b+1-a-1+b-1 = 5b -a +1
1)
2)
3)
6)
С модулями, если честно, не помню как решать:(
Пошаговое объяснение:
1)![1\frac{3}{8} - \frac{1}{2} =\frac{11-4}{8} = \frac{4}{8}](/tpl/images/1760/8514/0cd03.png)
2)![1\frac{3}{8} : \frac{1}{2} =\frac{11*2}{8} = \frac{11}{4}=2\frac{3}{4}](/tpl/images/1760/8514/a5f86.png)
3)![\frac{4}{5} :\frac{2}{3} -0.2= \frac{4*3}{5*2} -\frac{2}{10} = \frac{12-2}{10} =\frac{10}{10}=1](/tpl/images/1760/8514/37802.png)
4) (а+2b-4)+|-2|+а+2 = a+2b -4 +2 +a + 2 = 2a + 2b
5) (4b+1)-|-а-1|+b-1 = 4b+1-(a+1)+b-1 = 4b+1-a-1+b-1 = 5b -a +1
6)![\frac{4}{9} +\frac{1}{3} +\frac{1}{2} =\frac{4*2+6+9}{18} =\frac{23}{18} = 1\frac{5}{18}](/tpl/images/1760/8514/870a4.png)